First record of the cleptoparasitic bee genus Sphecodes from Puerto Rico (Hymenoptera: Halictidae) - Engel, Michael S.; Prado, Sara G. (Journal of Melittology, 2014)
The cleptoparasitic bee genus Sphecodes Latreille (Halictinae: Halictini) is recorded from Puerto Rico for the first time. Sphecodes (Austrosphecodes) tainoi Engel was previously known from western Cuba but is here recorded from a series of males and females captured in south-central, central, and western Puerto Rico. Images of the species are provided along with brief remarks on observed variations and possible future directions of study into their natural history.